2020
DOI: 10.1007/s00467-020-04535-1
|View full text |Cite
|
Sign up to set email alerts
|

Born with a solitary kidney: at risk of hypertension

Abstract: Background Subjects with a congenital solitary kidney (CSK) are believed to be at risk of hypertension due to their low number of nephrons. However, as CSK is a congenital abnormality of the kidney or urinary tract (CAKUT), subtle dysplastic changes contributing to hypertension cannot be excluded. Methods We retrospectively compared office blood pressure (OBP) and ambulatory blood pressure monitoring (ABPM) between two groups of children with CAKUT, aged 6-18 years: Group A with a CSK and Group B with two kidn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Similarly, La Scola et al (2016) observed that in a cohort of 146 children with a congenital SFK, only 5% of patients had hypertension at a mean age of 12 years and only 4% presented with proteinuria at a mean age of 6 years. However, a more recent study by La Scola et al (2020) found that 33% of SFK patients were hypertensive. This was based on ambulatory blood pressure measurement, which did show many cases of masked hypertension, similar to the KIMONO study ( Westland et al, 2014 ; La Scola et al, 2020 ).…”
Section: Clinical Outcomesmentioning
confidence: 95%
See 1 more Smart Citation
“…Similarly, La Scola et al (2016) observed that in a cohort of 146 children with a congenital SFK, only 5% of patients had hypertension at a mean age of 12 years and only 4% presented with proteinuria at a mean age of 6 years. However, a more recent study by La Scola et al (2020) found that 33% of SFK patients were hypertensive. This was based on ambulatory blood pressure measurement, which did show many cases of masked hypertension, similar to the KIMONO study ( Westland et al, 2014 ; La Scola et al, 2020 ).…”
Section: Clinical Outcomesmentioning
confidence: 95%
“…However, a more recent study by La Scola et al (2020) found that 33% of SFK patients were hypertensive. This was based on ambulatory blood pressure measurement, which did show many cases of masked hypertension, similar to the KIMONO study ( Westland et al, 2014 ; La Scola et al, 2020 ). The inconsistencies in cardiovascular and renal outcomes observed between studies may therefore reflect differences in study parameters such as inclusion criteria, selection bias, age of follow-up, and methods used to determine blood pressure, GFR and proteinuria.…”
Section: Clinical Outcomesmentioning
confidence: 95%
“…Patient characteristics such as sex and ethnicity could be involved. Most studies showed no association between sex and risk for kidney injury in SFK patients [4,6,[8][9][10][11][12]. One notable exception is the study by Alfandary et al in which male adolescents with SFK had a threefold higher risk of kidney injury compared to female patients [11].…”
Section: Risk Stratificationmentioning
confidence: 99%
“…[1][2][3] Patients with CSK maintained better GFR levels by developing better adaptation mechanisms 5 ; however, HT risk was higher or similar to those with ASK in different studies. 2,5,6 The risk of ambulatory or masked HT (AHT and MHT, respectively) is increased in cases with CSK (4). Arterial stiffness, which shows subclinical end-organ damage, is increased in cases with AHT and MHT, and may lead to increased central BP (cBP).…”
Section: Introductionmentioning
confidence: 99%